Longitudinal Comparison of Enzyme- and Laser-Treated Intervertebral Disc by MRI, X-Ray, and Histological Analyses Reveals Discrepancies in the Progression of Disc Degeneration: A Rabbit Study. (10th May 2016) - Fusellier, Marion; Colombier, Pauline; Lesoeur, Julie; Youl, Samy; Madec, Stéphane; Gauthier, Olivier; Hamel, Olivier; Guicheux, Jérôme; Clouet, Johann
Abstract : Regenerative medicine is considered an attractive prospect for the treatment of intervertebral disc (IVD) degeneration. To assess the efficacy of the regenerative approach, animal models of IVD degeneration are needed. Among these animal models, chemonucleolysis based on the enzymatic degradation of the Nucleus Pulposus (NP) is often used, but this technique remains far from the natural physiopathological process of IVD degeneration. Recently, we developed an innovative animal model of IVD degeneration based on the use of a laser beam. In the present study, this laser model was compared with the chemonucleolysis model in a longitudinal study in rabbits. The effects of the treatments were studied by MRI (T2-weighted signal intensity (T2wsi)), radiography (IVD height index), and histology (NP area and Boos' scoring). The results showed that both treatments induced a degeneration of the IVD with a decrease in IVD height and T2wsi as well as NP area and an increase in Boos' scoring. The enzyme treatment leads to a rapid and acute process of IVD degeneration. Conversely, laser radiation induced more progressive and less pronounced degeneration. It can be concluded that laser treatment provides an instrumental in vivo model of slowly evolving IVD degenerative disease that can be of preclinical relevance for assessing new prophylactic biological treatments of disc degeneration.